Treatment Strategies for Dopamine Agonist-Resistant and Aggressive Prolactinomas: A Comprehensive Analysis of the Literature - Sari, Ramazan; Altinoz, Meric A.; Ozlu, Eylem Burcu Kahraman; Sav, Aydin; Danyeli, Ayca Ersen; Baskan, Ozdil; Er, Ozlem; Elmaci, Ilhan (Hormone and Metabolic Research, 2021)
Despite most of the prolactinomas can be treated with endocrine therapy and/or surgery, a significant percentage of these tumors can be resistant to endocrine treatments and/or recur with prominent invasion into the surrounding anatomical structures. Hence, clinical, pathological, and molecular definitions of aggressive prolactinomas are important to guide for classical and novel treatment modalities. In this review, we aimed to define molecular endocrinological features of dopamine agonist-resistant and aggressive prolactinomas for designing future multimodality treatments. Besides surgery, temozolomide chemotherapy and radiotherapy, peptide receptor radionuclide therapy, estrogen pathway modulators, progesterone antagonists or agonists, mTOR/akt inhibitors, pasireotide, gefitinib/lapatinib, everolimus, and metformin are tested in preclinical models, anecdotal cases, and in small case series. Moreover, chorionic gonadotropin, gonadotropin releasing hormone, TGFβ and PRDM2 may seem like possible future targets for managing aggressive prolactinomas. Lastly, we discussed our management of a unique prolactinoma case by asking which tumors’ proliferative index (Ki67) increased from 5–6% to 26% in two subsequent surgeries performed in a 2-year period, exerted massive invasive growth, and secreted huge levels of prolactin leading up to levels of 1 605 671 ng/dl in blood.
Keywords: prolactinoma; aggressive; invasive; malignant; molecular endocrinology